Pelatihan Evaluasi Siswa Dalam Pembelajaran Bahasa Arab Melalui Quiz Wordwall Di Madrasah Aliyah Assullamy Langko - Nufus, Zakiatun; Suparmanto, Suparmanto; Rohim, Abdul; Pebriarianti, Deta; Anggun Zizasqia Gunawan, Baiq (Armala, 2024)
The aim of this study was to evaluate the effectiveness of using the Wordwall platform in improving student engagement and learning outcomes at the secondary school level. The research method used is a qualitative research method with an experimental approach, carried out at MA ASSULAMY Langko. The research subjects were 11 class X MA ASSULAMY Langko students. The research subjects were students' knowledge and teachers' abilities in using the Wordwall application in teaching and learning activities in the classroom using traditional learning methods and a control group. Data is collected through achievement tests, classroom observations, and student satisfaction surveys. Research shows that the use of Wordwall significantly increases student engagement and active participation during the learning process. Wordwall is a website-based application that can be used as a learning medium for interactive tests, pairs, random words, anagrams, and others. With so many features to choose from, you get versatility in providing educational materials. This application offers 18 templates that you can access for free.